Government Securitizing Effort of Online Harmful Content in Indonesia - Treviliana Eka Putri (LPPM Universitas Bina Sarana Informatika, 2023)
The emergence of the Internet and social media has altered the way individuals interact with each other. This has also led to the flourishment of user-generated content on many platforms, where platforms act as the medium or environment for users' posts and interactions. While these developments may contribute to bringing space for ensuring citizens' freedom of speech and expression, there are also cases where the very same environment is filled with 'harmful' content such as fake news, hate speech, online fraud, etc. The government along with other related stakeholders in the field has the responsibility to ensure such harmful contents do not manifest into offline harms. In handling these issues, the government has often utilized legal measures to apply sanctions for the platforms and or individual creators and restrict the spread of the contents. Using the securitization perspective, this study will look into the Indonesian government's current approach to tackling online harmful content. This study argues that the government has put the issue to a higher level, putting it into the national security agenda, which results in some extraordinary measures being applied in several instances. Nonetheless, this study suggests that it is important for the government and all related stakeholders to de-securitize the issue, putting it into everyday discussion and politics while ensuring the protection of citizens' rights.